Influence of a concurrent strength and endurance training intervention on running performance in adolescent endurance athletes: An observational study - Jones, T. W.; Shillabeer, B. C.; Ryu, J. H.; Cardinale, M. (Journal of Human Sport & Exercise, 2018)
The purpose of the present work was to present a case study on the influence of implementing a structured strength training intervention in adolescent middle distance athletes. An 8 wk strength training intervention was implemented concurrent to the group`s middle distance training. Prior to and following the intervention a testing battery was implemented and the following physical qualities were assessed: aerobic capacity, lactate threshold, economy, time trial performance, lower body power and vertical stiffness. The concurrent strength and endurance training intervention was an effective training paradigm for improving economy, running performance and strength phenotypes in elite adolescent middle distance athletes.